Propriedades psicométricas da versão brasileira do World Health Organization Disability Assessment Schedule (WHODAS 2.0) em indivíduos com neuropatia periférica diabética - Oliveira, Geyse Gomes de (2023)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus (DM) due to chronic hyperglycemia affecting thin and thick nerve fibers. DPN can be disabling and affect quality of life because of neuropathic pain, burning, tingling, pare sthesia, fatigue, cramping, and loss of protective sensation. Its complications can be ulceration, infection, osteomyelitis and foot amputation and contribute to high levels of morbidity and mortality, risk of falls, hospitalization and high financial cost s. There are tests and questionnaires for DPN screening, but there is no gold standard questionnaire in the Brazilian version based on the biopsychosocial model and the International Classification of Functioning, Disability and Health such as the World He alth Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), which was developed by the World Health Organization (WHO) and translated into a Brazilian version in 2015 to measure disability and functionality. There is already a version of the WHODAS 2.0 validated for people with DM in 2019, however, studies suggest that people with DPN experience more physical disabilities and disabilities when compared to individuals with DM without DPN , as well as having more time living with DM. The aim of this stu dy was to analyze psychometric properties to verify some psychometric properties of the Brazilian version of the WHODAS 2.0 with 36 items in people with DPN . 84 individuals diagnosed with type 2 DM participated in the validation study with data collection in hospital outpatient clinics. The distribution of data normality was verified using the Shapiro Wilk test and the internal consistency was attributed according to Cronbach's alpha. Spearman's coefficient was used to analyze the test retest reliability in the 7 day interval after the first interview. The criterion validity (convergent and divergent) was analyzed using the Spearman coefficient, through the correlation of the WHODAS 2.0 domains with the World Health Organization Quality of Life abbreviated v ersion (WHOQoL bref) and Neuropathy and Foot Ulcer Specific Quality Of Life (NeuroQol) and the Timed Up and Go (TUG), which assess functionality, quality of life generically and specifically, and risk of falling, respectively). The result showed adequa te internal consistency for the WHODAS total score, ranging from a lower value in the interpersonal relationships domain, which increased the value by eliminating the sexual relationship item, and a higher value in the participation domain. Strong reliabil ity was found across test retest, with the most stable domains being mobility and participation, respectively. In the WHODAS criterion validity, the correlations were moderate with the WHOQoL bref, moderate and high with NeuroQoL and low with TUG. Thus, we can infer that the WHODAS 2.0 is a reliable instrument and there are indications that it is valid in the Brazilian version in individuals with DPN